Effect of using The interactive method and guided discovery in Learn the skill of backhand ground tennis - Abdul ameer, Lamia (Journal of Physical Education, 2019)
The purpose of this study in the selection of The style guided discovery and interactive to learn a skill strike, front and rear floor tennis for being appropriate for the goals desired levels for the growth of the students and the capabilities available and content material lesson and when used by the teacher will be consistent with his vision for education, while the research problem is the lack of pay most interested in the process instruction in multi- use methods teaching diverse and restrict the values ​​of research to see which ones best impact on the level of student learning and especially that the game takes advanced educationally and artistically from all sides, and that the researcher selected sample of (30) students, and concluded that the use of style interactive and guided discovery an impact in learning a skill background strike tennis and interactive style has a greater effect in learning the skill of the back of the strike guided discovery style, and recommended to carry out a study taking other skills and use other methods to detect preference in the education of students.